2019
DOI: 10.1016/j.cocis.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging collective effects in externally driven colloidal suspensions: experiments and simulations

Abstract: In this review article, we focus on collective motion in externally driven colloidal suspensions, as well as how these collective effects can be harnessed for use in microfluidic applications. We highlight the leading role of hydrodynamic interactions in the self-assembly, emergent behavior, transport, and mixing properties of colloidal suspensions. A special emphasis is given to recent numerical methods to simulate driven colloidal suspensions at large scales. In combination with experiments, they help us to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 183 publications
(278 reference statements)
0
48
0
Order By: Relevance
“…Turbulent-like flows in bacteria and sperm suspensions [6][7][8][9], and phase synchronization between flagella [10] are illustrative examples in natural systems. Colloidal particles have been designed to mimic the behavior of natural systems at both the individual and collective level [11,12], and also to explore alternative ways to mix the surrounding fluid or to transport particles at low Reynolds number [13][14][15]. In particular, recent experiments and simulations have shown that suspensions of torque-driven particles above a floor could self-assemble into stable motile structures, called "critters", that have no analog in natural systems [16], see Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Turbulent-like flows in bacteria and sperm suspensions [6][7][8][9], and phase synchronization between flagella [10] are illustrative examples in natural systems. Colloidal particles have been designed to mimic the behavior of natural systems at both the individual and collective level [11,12], and also to explore alternative ways to mix the surrounding fluid or to transport particles at low Reynolds number [13][14][15]. In particular, recent experiments and simulations have shown that suspensions of torque-driven particles above a floor could self-assemble into stable motile structures, called "critters", that have no analog in natural systems [16], see Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The physics of torque-driven colloidal particles (called microrotors) have recently attracted significant attention [13,15,17]. Microrotors can be driven with an external rotating magnetic field [16,18], or by using a Quincke-like instability under the action of an electric [19] or magnetic field [20].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting overdamped dynamics can therefore be adequately described within the framework of linear hydrodynamics [93,94]. Accordingly, the translational velocity of the membrane particles V i is linearly coupled to the forces acting on their surfaces via the hydrodynamic mobility functions [95][96][97][98]. The latter are second-order tensors, which simply reduce to scalar quantities when considering motion in an unbounded medium and neglecting the fluid-mediated hydrodynamic interactions between the particles.…”
Section: System Setupmentioning
confidence: 99%
“…1 Introducing colloidal suspensions into such structures introduces an extra level of complexity, and is also of high technological relevance in filtration, separation, or assisted concentration of colloids. 2 Examples of this can be found in fields ranging from oil recovery 3 to food processing. 4 The interaction between channel walls and the (often charged) colloidal particles (CPs) initiates a range of multi-scale processes, 5 complicating the rational design of fluid processing and lab-on-chip devices.…”
Section: Introductionmentioning
confidence: 99%